Serat Jute Dengan Olahan Kriya Sebagai Alternatif Bahan Baku Tas - Murwanti, Aprina (Prosiding Pendidikan Teknik Boga Busana, 2021)
Jute (gunny) nowadays is only popular as material of gunnysack, carpet lining, or used to layering the door mat. After been threaten and explored, jute assuming as an appropriate fabric and can be used as primary material of handbags without losing its unique characteristic. The craftsmanship skills and esthetical design have been used in the exploration process. Jute fiber that been processed, now can proudly used an alternative material for handbag production. Inother hand, using jute as bags material also can contribute jute consumption and support creative industry movement as goverment program.